LC-MS/MS method for the simultaneous determination of tenofovir, emtricitabine, elvitegravir, and rilpivirine in dried blood spots - Prathipati, Pavan Kumar (Biomed Chromatogr, 2018)
A simple, short, and rugged LC-MS/MS method for the simultaneous determination of tenofovir, emtricitabine, elvitegravir and rilpivirine was developed and validated. Dried blood spots were prepared with 25 μL of spiked whole blood. A 3 mm punch was extracted with methanol containing labeled internal standards. Ten microliter was injected into LC-MS/MS using isocratic mobile phase composed of 0.1% formic acid in water and 0.1% formic acid in acetonitrile (45: 55 v/v) at a flow rate of 0.25 mL/min. The method was validated in the range of 10 to 2000 ng/mL for all four analytes. The intra-assay accuracy (%RE) of the method was −4.73 to 4.78, 1.35 to 2.89, −8.89 to −0.49 and −1.40 to 1.81 for tenofovir, emtricitabine, elvitegravir and rilpivirine respectively. The inter-assay accuracy was within ± 15% of nominal and precision (%CV) was < 15%. The hematocrit effect on quantification was non-significant at the tested hematocrit levels (35 to 70%). The DBS method had shown good agreement with plasma method, hence can be used as an alternative to plasma method.